2015
DOI: 10.15261/serdj.22.187
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Carbon Dioxide Extraction of Xanthones from the Pericarps of <i>Garcinia Mangostana</i> Linn. Enhanced by Ultrasonic Irradiation

Abstract: The liquid carbon dioxide (CO 2 ) extraction of xanthones, such as α-mangostin from the pericarp of mangosteen (Garcinia mangostana Linn.), was enhanced using ultrasound at 5, 20 and 25 ºC. Mixtures of carbon dioxide and ethanol were used as solvents. The extraction pressure was from 8 to 14 MPa. To enhance the extraction yield, the solvent was irradiated with ultrasound. The yields of xanthones, such as α-mangostin, in the extraction were significantly improved without any change in the selectivity of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Taps are opened on the gas cylinder (6) and the control panel (2), and gas flows from the cylinder to the internal space until the pressures inside the cylinder and reactor equalize. The pump (7) then raises the pressure to the required level, and the line from the control panel to the reactor is closed. Afterwards, the tap on the cylinder is closed as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taps are opened on the gas cylinder (6) and the control panel (2), and gas flows from the cylinder to the internal space until the pressures inside the cylinder and reactor equalize. The pump (7) then raises the pressure to the required level, and the line from the control panel to the reactor is closed. Afterwards, the tap on the cylinder is closed as well.…”
Section: Methodsmentioning
confidence: 99%
“…The potential of carbon dioxide applications for extraction has been well-studied [7][8][9][10]. Studies of the effect of ultrasound (US) on extraction processes have shown that the penetrating power of carbon dioxide increased under the effect of US both in the subcritical and supercritical states.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the high content of bioactive metabolites such as xanthones, triterpenes, and benzophenones (Nguyen et al, 2005;Mohamed et al, 2014). However, most of the earlier research in mangosteen has mainly focused on xanthones without much emphasis on other potential bioactive metabolites in mangosteen fruit pericarp including primary metabolites (Sukatta et al, 2013;Mishima et al, 2015;Yoswathana and Eshtiaghi, 2015). Hence, further study to profile mangosteen metabolome from the pericarp and optimizing its extraction methods are needed, particularly using the metabolomics approach.…”
Section: Introductionmentioning
confidence: 99%
“…SC-CO2 is excellent extraction solvent for the non-polar substance because it has properties similar to hexane. Additionally the method has shown high selectivity by operating conditions such as temperatures and pressures [13][14][15]. However, it is necessary to use a special apparatus to establish the high pressure of SC-CO2 and pretreatment such as sample drying.…”
Section: Introductionmentioning
confidence: 99%